High-Resolution Melting Analysis Potential for Saccharomyces cerevisiae var. boulardii Authentication in Probiotic-Enriched Food Matrices - Monika Borkowska; Michał Kułakowski; Kamila Myszka (BioTech)
To date, the only probiotic yeast with evidence of health-promoting effects is Saccharomyces cerevisiae var. boulardii. The expanded market including dietary supplements and functional foods supplemented with Saccharomyces cerevisiae var. boulardii creates an environment conductive to food adulterations, necessitating rapid testing to verify product probiotic status. Herein, qPCR-HRM analysis was tested for probiotic yeast identification. The effectiveness of the primer pairs’ set was examined, designed to amplify heterogeneous regions in (a) rDNA sequences previously designed to identify food-derived yeast and (b) genes associated with physiological and genotypic divergence of Saccharomyces cerevisiae var. boulardii. Preliminary tests of amplicons’ differentiation power enabled the selection of interspecies sequences for 18SrRNA and ITS and genus-specific sequences HO, RPB2, HXT9 and MAL11. The multi-fragment qPCR-HRM analysis was sufficient for culture-dependent Saccharomyces cerevisiae var. boulardii identification and proved effective in the authentication of dietary supplements’ probiotic composition. The identification of S. cerevisiae var. boulardii in complex microbial mixtures of kefir succeeded with more specific intragenus sequences HO and RPB2. The predominance of S. cerevisiae var. boulardii in the tested matrices, quantitatively corresponded to the probiotic-enriched food, was crucial for identification with qPCR–HRM analysis. Considering the reported assumptions, qPCR-HRM analysis is an appropriate tool for verifying probiotic-enriched food.